Stereoselective Synthesis of Mechanically Planar Chiral Rotaxanes. (17th October 2018) - Jinks, Michael A.; de Juan, Alberto; Denis, Mathieu; Fletcher, Catherine J.; Galli, Marzia; Jamieson, Ellen M. G.; Modicom, Florian; Zhang, Zhihui; Goldup, Stephen M.
Abstract: Chiral interlocked molecules in which the mechanical bond provides the sole stereogenic unit are typically produced with no control over the mechanical stereochemistry. Here we report a stereoselective approach to mechanically planar chiral rotaxanes in up to 98:2 d.r . using a readily available α‐amino acid‐derived azide. Symmetrization of the covalent stereocenter yields a rotaxane in which the mechanical bond provides the only stereogenic element.